`Effectiveness of topical application of aloe vera gel on radiation induced mucositis in patients receiving radiotherapy for head and neck malignancies - Lakhani, Rita (International Journal of Nursing Research, 2023)
Abstract: In recent years, the treatment of radiotherapy is commonly and concomitantly prescribed for patients with head and neck cancer. Radiotherapy is associated with high rates of mucotoxicity with no consensus/universal standard of its care. Aim: The objective of this study (part-publication) is to assess the effectiveness of topical application of aloe vera gel in the magnitude of increasing radiation-induced mucositis in malignant patients of head and neck. Materials and Methods: A triple-blind, control group design was adopted on 40 eligible respondents scheduled to receive conventional radiotherapy. The respondents were classified randomly between Group A and Group B; one among them being the experimental group using the drug aloe vera and the other group being the control group using base gel. Standardized tools were applied to assess the primary and secondary outcome of development of radiation induced mucositis. Results: Respondents in two groups were statistically identical in baseline characteristics (P>0.05). The radiation-induced mucositis grades were clinically less and not significant for Group A as compared to Group B (P>0.05). Further, by the end of treatment, two groups were statistically same in the maximal grade of toxicity (Z = 2.7, P>0.05), use of drugs, QOL scores, the percentage of weight loss and nutritional status. Conclusion: The researcher is blind to the allocation of the tubes but since, both the groups are same along various assessment parameters it can be safely concluded that aloe vera was not beneficial in reducing the magnitude of increasing radiation-induced mucositis. The Groups identity was revealed at the end of the main study; Group A was identified as the experimental group and Group B was the control group.